Meningkatkan Budaya Literasi Membaca Siswa Kelas VI dengan Pemanfaatan Pojok Baca - Titi Agustinah; Siti Rochmiyati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This research was conducted based on the low reading culture of class VI students being a serious symptom for the continuity of learning in the classroom. Improving reading culture in students must be nurtured and nurtured from an early age and is a continuous process so that their reading culture grows and develops by utilizing reading corners. The aim of this research is to determine the increase in reading culture of class VI students by using a reading corner. The type of research used in this research is descriptive qualitative with research methods in the form of observation and literature study. The research subjects were class VI students and the research object was the use of reading corners. The aim of using a reading corner is to stimulate students to be more fond of reading, to bring books closer to students, at any time students can read books without having to visit the library, as part of learning activities, to condition the class so that it is not noisy, to support independent learning activities, to provide opportunities to students to improve reading culture, develop thinking power, and enrich students' learning experiences.